A three-wave panel study on longitudinal relations between problematic social media use and psychological distress during the COVID-19 pandemic. (November 2022) - Di Blasi, Maria; Salerno, Laura; Albano, Gaia; Caci, Barbara; Esposito, Giovanna; Salcuni, Silvia; Gelo, Omar Carlo Gioacchino; Mazzeschi, Claudia; Merenda, Aluette; Giordano, Cecilia; Lo Coco, Gianluca
Highlights: To examine bi-directional associations between PSMU and distress. The link between PSMU and distress is mainly driven by trait-like differences. No within-person cross-lagged associations between PSMU and distress. PSMU may represent a correlate rather than a determinant of psychological distress. Abstract: Background: It still remains unclear whether problematic social media use (PSMU) is a cause or a consequence of psychological distress. The present study aimed to investigate the temporal relationships between PSMU and psychological distress through a three-wave panel study (between April and July 2020, with an interval of 1 month between each period of time). Methods: 3, 912 adult Italian participants were surveyed during the COVID-19 pandemic for psychological distress (Depression, Anxiety and Stress Scale) and PSMU (Bergen Social Media Addiction Scale). Random-Intercept Cross-Lagged Panel Models were applied to disaggregate between-person from within-person associations as regards PSMU and an individual's distress. Results: On a between-person level we found that adults with higher PSMU also reported heightened levels of psychological distress across the three waves. However, on a within-person level, no cross-lagged associations were found between changes in distress and subsequent changes in PSMU and vice versa. The results were largely unchanged with the inclusion of participants' gender and age or COVID-19-related fears as covariates, and when the three subscales of depression, anxiety and stress were examined in separate models. Conclusions: The current study suggests that the link between PSMU and psychological distress is mainly driven by trait-like differences and not by state-like individual changes over time.